Flat Prices, Cell Phone Base Stations, and Network Structure: An Instrumental Variable Approach to Endogenous Locations - Andreas Mense; Benjamin Wirth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Following the critique of Pinkse & Slade (2010) and Gibbons & Overman (2012), we develop an instrument for the estimation of local price effects of cell phone base stations (CPBS) in an urban area. The instrument is derived from the spatial structure of the network and technical and regulatory requirements. Such a strategy could be useful in other contexts in which location choice is endogenous but depends on an existing network structure. We find a significantly negative impact of nearby CPBS on flat prices. The discount amounts to 3.3% of a property s value when two similar flats at distances of 50 and 100 m to the nearest CPBS are compared. The small difference between OLS and IV results suggests that the distance to the nearest CPBS is not endogenous, in opposition to Brandt & Maennig (2012).
Keywords: R39; Q51; Q53; 330